Determination of the mechanosynthesis conditions of the Mg ñ MgO reaction region - Martínez García, Alfredo; Navarro Martinez, Ana Karin; Aparicio Saguilan, Alejandro; Valera Zaragoza, Mario; Avalos-Borja, M.; Juárez Arellano, Erick Adrián (Trade Science, 2015)
This study deals with the prediction, by a mathematical model, and the corresponding experimental confirmation of the mechanochemical synthesis conditions of MgO. The ball milling processis a easy to implement in industry process but that involvesseveral parameters which make it very complex to identify the optimum operating conditions. It was established that the reaction zone of MgO is between accumulative energies of 41 to 64 MJ/mol regardless of the grinding material or the conditions used.Above thisregion only MgO is obtained. It is necessary to have energies between 24 and 48 Wh/g and to have energies of impact greater than 0.025 J/hit to trigger the mechanochemical synthesis of MgO.
Keywords: Mecanosíntesis; Molino de bolas de alta energía